Research of worm-propagation prediction based on stochastic experiment - LIU Ting1; ZHENG Qin-hua1; GUAN Xiao-hong1; QU Yu1; WANG Na1 (Tongxin xuebao)
The prediction of the worm propagation is the basis of the worm defense.It is becoming more difficult to model the propagation of worms in the early stage of worm-spreading,because the worm strategies are smarter and the Internet structure is more complicated than ever before.In present study,a stochastic simulator was designed to simulate the propagation of worms.From the analysis of 1000 groups of experiment results,it was proved that the worm-propagation is a stochastic process,and the correlation coefficient between each group of results is close to 1.Therefore,a new prediction method was proposed,which could accurately calculate the propagation of worm when 0.1% of all vulnerable hosts were infected.